Effective Short-Video Platform Advertising on Chinese Consumers’ Online Purchase Intention - Mengyan Sheng,; Norazlyn Kamal Basha,; Anusuiya Subramaniam,; Raja Nerina Raja Yusof, (Al-Qanṭara, 2025)
Chinese consumers have been actively involved in the revolutionary shift of digital advertising techniques brought about by the rise of short-video mediums. Given the market dominance of platforms such as Douyin as well as Kuaishou, it is imperative to comprehend the effect of short-form video marketing on the intent to buy something online. The dynamic as well as captivating quality of brief videos offers a special chance to affect customer behavior. In the backdrop of China, the precise mechanisms underlying this influence are still insufficiently understood. Therefore, the goal of this research study is to investigate how Chinese consumers' intentions to make online purchases are affected by short-video channel advertising. The goal of the research is to identify the relationships that influence consumer choices. The quantitative methodology was considered the most suitable strategy for this investigation. The results of the research study showed that bandwagon perception and conventional interactivity had significant effects on online purchase intentions of consumers. Similarly, flow experience had a significant mediating impact on the relationships among bandwagon perception, interactivity, and online purchase intent. However, consumer attitude is influenced by external factors such as political developments, public health emergencies, or financial circumstances. These outside factors have not been considered in the study.